Solar-pumped tem00 mode nd:yag laser - Liang, Dawei (2021)
These research projects were funded by the Science and Technology Foundation of Portuguese Ministry of Science (PTDC/FIS/103599/2008 and PTDC/FIS/122420/2010), Technology and Higher Education (FCT-MCTES).